A high-sensitivity long-lifetime phosphorescent RIE additive to probe free volume-related phenomena in polymers. Issue 11 (18th January 2023) - Dini, Valentina Antonia; Gradone, Alessandro; Villa, Marco; Gingras, Marc; Focarete, Maria Letizia; Ceroni, Paola; Gualandi, Chiara; Bergamini, Giacomo
Abstract : The photophysical behaviour of phosphorescent rigidification-induced emission (RIE) dyes is highly affected by their micro- and nanoenvironment. This is exploited to monitor physical ageing and mechanical stresses in polymers. Abstract : The photophysical behaviour of phosphorescent rigidification-induced emission (RIE) dyes is highly affected by their micro- and nanoenvironment. The lifetime measure of RIE dyes dispersed in polymers represents an effective approach to gain valuable information on polymer free volume and thus develop materials potentially able to self-monitor physical ageing and mechanical stresses.